Alcances, limites e avanços do fundo constitucional de financiamento do Centro-Oeste: Uma análise espaço-estrutural das regi\~oes imediatas do estado de Mato Grosso do Sul - Murilo José de Souza Pires; Gislaine de Miranda Quaglio; Rodrigo Portugal (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– The Constitutional Funds were established by art. 159, item I, paragraph c of the Federal Constitution of 1988 with the objective of contributing to the "reduction of inequalities" existing between the peripheral regions of the North, Northeast and Center-West vis-à-vis the central regions of the Southeast and South. In this sense, its role as a financier of productive investments in these peripheral regions has increased in recent decades. Therefore, the objective of this investigation was to understand the spatial profile (municipalities and immediate regions) of Mato Grosso, through some socioeconomic variables, in which FCO disbursements were distributed between 2002 and 2018. Additionally, to verify how the FCO variables and GDP behaved in the same period in certain regions with different profiles in the period from 2002 to 2018. Therefore, the argument woven in the work started from the premise that the Mato Grosso productive structure is marked by an economic formation rooted in a late economy, underdeveloped, dependent and, therefore, it presents a structural heterogeneity that sets limits to the reach and depth of penetration of technical progress in Mato Grosso's productive units. Finally, it is observed that, it is observed that the municipal groups reconstructed as thought concrete express structures that reproduce patterns of an underdeveloped economy, which is marked by a structural and productive heterogeneity, in which they coexist, in the same space and time, the modern and the backward, that is, productive units that have been gripped by the modernizing forces of technical progress, as well as others that are still rooted in traditional and subsistence economies. For example, Três Lagoas is a specific, but not unique, case of a pattern of capital reproduction, in space and time, through the pulp and paper complex, which reinforces the argument that the resources directed by the FCO are aligned with localities that the productive units are integrated as several market structures, but with low integration to the neighborhood. In other words, the FCO's resources are reinforced to robust structures with links in national and international production chains, but which have structures for significant limits in the immediate region. On the other hand, the average changes, more tenuous, such as a series of GDPpc, even though the region has a more rigid structure. These localities are found on the margins of the growth process or regions of increments of Matosense, it is verified that the fractions of F are possibly influenced by the internal product of these captain localities that do not follow a pattern.
Keywords: R11; 330; Constitutional Fund of the Midwest; structural heterogeneity; Mato Grosso do Sul